Preparation of Titanium Phosphate as Solid Electrolyte Material for Secondary Battery - Handoko Setyo Kuncoro; Suhanda S; Muhammad Syaifun Nizar; Ratih Resti Astari; Didit Nur Rahman; Evvy Kartini; Bambang Prihandoko (Balai Besar Keramik, 2018)
Industrialization of lithium batteries in Indonesia requires in addition to mineral technology as well as local raw material support. Solid electrolytes are one of the lithium battery cell components that determine the working stability (long life-time) of the battery and the safety of its use. In this study solid electrolyte for secondary battery with type of Lithium Aluminum Titanium Phosphate (LATP) was synthesized in variation of LATP.n% Li2O where Li2O functioned as conductivity enhancing additive with n=0,5,10. Theoretically, the largest LATP solid electrolyte content is the Titanium Phosphate (TiP) material about 80% by weight fraction, the material can be obtained from natural mineral materials such as ilmenite and apatite in Indonesia. It has qualified for the industrialization of battery components with domestic component level (TKDN) material exceeding 60%. The TiP material was prepared by sintering destruction and acid-base methods, while the LATP.n% Li2O was made using powder metallurgy and sintering method with pre-heating 400 ° C. The XRD test result shows a diffraction pattern of TiP similar to TiP pattern from other publication reference. A slight difference in the XRD pattern indicated an excess of TiO2 rutile content in TiP material and other impurities, which has also been proven by XRF test results. The SEM test result provided a micrograph showing off the crystal blocks corresponding to the shape described by other references. The LATP material made has a single and stable ionic conductivity mechanism based on the interpretation of the Cole-cole plot diagram. The result of ionic conductivity test for LATP.n% Li2O showed variation with n = 5 having conductivity (4.5x10-5 S / cm) higher than other variations.